2003
DOI: 10.1136/tc.12.3.310
|View full text |Cite
|
Sign up to set email alerts
|

Persistent use of nicotine replacement therapy: an analysis of actual purchase patterns in a population based sample

Abstract: Background: In 1996, the US Food and Drug Administration (FDA) approved switching nicotine gum and patch from prescription to over-the-counter (OTC) status. Some expressed concerns that broader availability and lack of physician control might increase persistent use of nicotine replacement therapy (NRT)-that is, use beyond the period specified by the FDA approved label. Objective: To estimate the incidence of persistent use of OTC nicotine gum and patch for periods of > 3 months, > 6 months, > 12 months, and >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 38 publications
1
50
0
1
Order By: Relevance
“…It is of interest to note that the authors excluded long -term patch users since it would have been unlikely to see a difference between active and placebo treatment due to the ease by which they normally can stop. Moreover , it is much more infrequent to observe long -term patch use ( Shiffman, Hughes, Pillitteri, & Burton, 2003 ). It seems as a patch is not very likely to be able to support a compulsive use pattern due to its little behavioral involvement and or pharmacokinetic nicotine uptake pattern.…”
Section: Dependence On Tobacco and Nicotine Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is of interest to note that the authors excluded long -term patch users since it would have been unlikely to see a difference between active and placebo treatment due to the ease by which they normally can stop. Moreover , it is much more infrequent to observe long -term patch use ( Shiffman, Hughes, Pillitteri, & Burton, 2003 ). It seems as a patch is not very likely to be able to support a compulsive use pattern due to its little behavioral involvement and or pharmacokinetic nicotine uptake pattern.…”
Section: Dependence On Tobacco and Nicotine Productsmentioning
confidence: 99%
“…This is most likely the reason why it is very unusual to see longterm use of patch. However , cases exist ( Shiffman et al, 2003 ) in which nicotine patch use persists. If that can be taken as an indicator of dependence , one can speculate that the type of dependence might be of a different sort than the one to cigarettes.…”
Section: Nicotine and Tobacco Researchmentioning
confidence: 99%
“…One of the arguments against deregulation was that the easier access to NRT products could lead to misuse and dependence on these products. However, Shiffman et al [21] reported that persistent use of NRT products is very rare and did not increase with the transition to OTC use in the USA. In fact NRT products were more often used for shorter lengths of time than recommended.…”
Section: Discussionmentioning
confidence: 96%
“…Among the most important barriers are scepticism towards NRT effectiveness; fear of addiction [20,21]; health care providers' reluctance to get involved and support SC [22,23]; and the price of the NRT products [24]. Also several other problems related to the use of NRT exist, which underline the importance of the guidance and support given by health care professionals [3,5,6,10,20,[25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Have Noticed That Minors Have Abused Nrt Productsmentioning
confidence: 99%